The Nature of Indifference Curves - Allen, R. G. D. (Review of Economic Studies, 1934)
Journal Article The Nature of Indifference Curves Get access R. G. D. Allen R. G. D. Allen London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 110–121, https://doi.org/10.2307/2967617 Published: 01 February 1934